SISTEM PEMBINAAN NARAPIDANA LEMBAGA PEMASYARAKATAN DALAM KAJIAN HUKUM PIDANA ISLAM - Soliha, Ulfa Safira; A., Zulkarnain M. (Legal Standing : Jurnal Ilmu Hukum, 2024)
Nowadays, the number of crimes or criminality is increasing. This is due to economic factors, low education, and the lack of understanding of the Indonesian people about the laws in their own country. Criminal offenders or prisoners must take responsibility for the actions they have committed, by serving a prison sentence based on a court verdict. This research aims to find out how the prisoner coaching system provided by the Medan Class 1 Correctional Institution is then associated with the prisoner coaching system in the study of Islamic Criminal Law, and the obstacles faced by the Correctional Institution in fostering prisoners. This research method is field research with qualitative research type and empirical juridical or socio legal approach. The results showed that the inmate coaching system at Class 1 Medan Correctional Institution has 2 types of coaching, namely personality coaching and independence coaching, as for the coaching of prisoners in Islamic criminal law, namely: fostering faith values and coaching by means of repentance. Then the obstacles faced by the Correctional Institution are in the coaching activities not a few of the inmates who are lazy to follow the coaching, overcapacity and lack of correctional officers to supervise and control and foster inmates in the Correctional Institution.